THE EMBODIMENT OF ADAT LAW AS AN ELEMENT OF LEGAL CERTAINTY IN ADMINISTRATION OF ADAT RIGHTS - Gunadi, Anne (Indonesia Law Review, 2019)
Former Adat land is formed based on the assessment of Adat Law, not because of state granting or land registration, and the Agrarian Basic Law recognizes it through provisions on conversion provisions, where former customary land rights are converted into ownership rights if the subject is an Indonesian citizen. The registration of former adat land rights aims to guarantee legal certainty, by abolishing former customary land, and being converted to ownership rights, with the issuance of certificates of land rights, which are formally subject to the system of control over land regulated in Agrarian Basic Law. Before the enactment of the Agrarian Basic Law, on customary land, only a fiscal cadastre was carried out, for the purpose of collecting land taxes, with evidence of girik, kekitir, petuk, kohir or excerpt from letter C, for adat land located in villages or Indonesian respondents for adat land in the city. From the point of proof of former adat land rights, consisting of complete written evidence, incomplete written evidence or no written evidence at all, carried out in 2 two) the procedure for registering former adat land rights is a conversion confirmation procedure only for complete written evidence and procedure for recognition of rights followed by conversion, for written evidence that is incomplete or non-existent at all. Legal uncertainty in registering former adat land rights is due to legal actions or events that have occurred since the enactment of the Basic Agrarian Law until the last rights holder is not recorded in the land book in the village or kelurahan, so the community or village head does not know the land history, legal subject the object of the plot of land and the legal relationship that occurs relating to the control of the land. In overcoming this legal uncertainty, using normative juridical methods, the principle of adat law was reduced to legal principles, which were used as parameters for head of adat or village heads in determining legal certainty regarding the legal status of adat land, legal subjects, land objects, legal relations relating to control of adat land as well as in the management of land book administration in the village or kelurahan that is open to the public.